Faktor-Faktor yang Mempengaruhi Kinerja Keuangan pada Sektor Pertambangan - Humaidi, Fachliya Salsabila; Arisman, Anton (MDP Student Conference, 2024)
This research aims to examine the influence of intellectual capital and corporate social responsibility on the financial performance of mining companies listed on the Indonesia Stock Exchange. This type of research is quantitative research, the data source in this research is secondary data obtained from the BEI. The number of samples used in the research was 14 mining companies. The sample selection method used is purposive sampling, which is a sampling technique based on certain criteria determined by the researcher. The results of hypothesis testing in this research show that intellectual capital has an effect on financial performance and corporate social responsibility has an effect on financial performance in mining companies listed on the Indonesia Stock Exchange